Instruments measuring the quality of life among people living with type 2 diabetes mellitus in India: a systematic review protocol. Issue 4 (2nd April 2021) - Demla, Chetna; Thomas, Anns; Jose, Jomol; Joshy, Angela L; Hrishikesh, M A; Rajendran, Ambigai; Parsekar, Shradha S
Abstract : Introduction: Type 2 diabetes mellitus affects an individual's quality of life (QoL); and there are multiple instruments that can be used to measure QoL. The purpose of this systematic review is to identify the existing instruments that have been used to measure QoL in people living with diabetes, and to enlist the major domains (such as physical and psychological components) available in the identified instruments. Additionally, we plan to determine the psychometric properties of the identified QoL instruments using COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) methodology. Methods and analysis: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocol guideline was followed to report this systematic review protocol. Searches will be conducted on MEDLINE (via PubMed, Web of Science), SCOPUS and CINAHL. Predetermined inclusion/exclusion criteria will be applied to the search results, to include studies with adult individuals diagnosed with type 2 diabetes mellitus, with and without complications, and exclude studies with type 1 diabetes or other clinical illness. Studies conducted outside India will be excluded. Five authors in pairs will independently screen the articles and extract the data that meets the inclusion criteria. The COSMIN criteria will be used to assess the risk of bias of included studies. Narrative synthesis will be performed to analyse the findings of the instruments. Ethics and dissemination: Ethical permission is not applicable, as this is a systematic review. We intend to disseminate the systematic review findings through a national or international conference and publish the findings in a peer-reviewed journal. PROSPERO registration number: CRD42020180432.